Knowledge Management as a Determining Factor in the Retention of Professionals in the Industry: A Case Study in an Organization in the Furniture Industry - Osmarina Pedro Garcia Garcia; Sandra Maria Coltre (BBR: Brazilian Business Review, 2017)
This study investigates which one(s) of the knowledge management factor(s), via the tacit and/ or explicit way, are crucial in retaining professionals in a company in the furniture industry. The research was exploratory, with lifting procedure, and qualitative and quantitative approach. Data were collected from June to August 2014 in a furniture industry of Francisco Beltrão/PR, through a questionnaire applied to 224 employees of administrative, industrial and commercial areas, as follows: 11 managers, 44 responsible for the area and 169 operational employees. The Likert scale detected the frequency of respondents’ views. To provide consistency to the findings, the data obtained Multivariate Analysis statistical treatment, developed in the free R software. We applied the Main Component Analysis, Factorial Analysis, Correspondence Analysis, Correlation Analysis and Chi-squared Test separately for tacit and explicit ways. After the analysis, we concluded that through the factors shown in the study, both pathways influence the retention of employees of the surveyed company.